Heme oxygenase-1 alleviates ischemia/reperfusion injury in aged liver - Wang, Xue-Hao (World J Gastroenterol, 2005)
AIM: To investigate if ischemia/reperfusion (I/R) injury in aged liver could be alleviated by heme oxygenase-1 (HO-1). METHODS: Three groups of SD rats (16 mo old) were studied. Group 1: control donors received physiological saline 24 h before their livers were harvested; group 2: donors were pretreated with hemin 24 h before their livers were harvested; and group 3: donors received hemin 24 h before their livers were harvested and zinc protoporphyrin (ZnPP, HO-1 inhibitor) was given to recipients at reperfusion. The harvested livers were stored in University of Wisconsin solution (4 °C) for 6 h, and then transplanted to syngeneic rats. Serum glutamic oxaloacetic transaminase (SGOT), apoptotic cells, and apoptotic gene were measured 3, 6, 12, 24, 48 h after reperfusion. We measured the apoptotic index by TUNEL, determined the expression of antiapoptotic Bcl-2 and proapoptotic (caspase-3) gene products by Western blot. RESULTS: After 3, 6, 12, 24, and 48 h of reperfusion, the SGOT levels (584.4±85.8 u/L, 999.2±125.2 u/L, 423.4±161.3 u/L, 257.8±95.8 u/L, and 122.4±26.4 u/L) in hemin group were significantly (all P<0.05) lower than those in saline group (1082.2±101.2 u/L, 1775.2±328.3 u/L, 840.4±137.8 u/L, 448.6±74.3 u/L, and 306.2±49.3 u/L). Liver HO-1 enzymatic activity correlated with beneficial effects of hemin and deleterious effects of adjunctive ZnPP treatment. Markedly less apoptotic (TUNEL+) liver cells 3, 6, 12, 24, and 48 h after reperfusion (5.16±0.73, 10.2±0.67, 9.28±0.78, 7.14±1.12, and 4.78±0.65) (P<0.05) could be detected in hemin liver grafts, as compared to controls (7.82±1.05, 15.94±1.82, 11.67±1.59, 8.28±1.09, and 6.36±0.67). We detected the increased levels of Bcl-2 (1.5-fold) expression and compared with saline controls. These differences were most pronounced at 12 h after transplantation. In contrast, an active form of proapoptotic caspase-3 (p20) protein was found to be 2.9-fold lower at 24 h in hemin-pretreated group, as compared to saline liver transplant controls. CONCLUSION: HO-1 overexpression can provide potent protection against cold I/R injury. This effect depends, at least in part, on HO-1-mediated inhibition of antiapoptotic mechanism.